L'énigme autodidacte. - Laubard, Charlotte; Quoi, Alexandre; Dayras, Arthur (s.l. ; Saint-Étienne : Éditions Snoeck : Les amis du Musée d'art moderne et contemporain de Saint-Étienne métropole, 2021)
Darger, Henry ; Boetti, Alighiero ; Tichý, Miroslav ; Bruly, Bouabré, Frédéric ; Ademeit, Horst ; Scott, Judith ; Cuoghi, Roberto ; Kunz, Emma ; Palanc, Francis ; Keïta, Seydou ; Odermatt, Arnold ; Piacentino, Giani ; Fillou, Robert ; Raynaud, Jean-Pierre ; Sanejouand, Jean-Michel ; Panchounette, Présence ; Bijl, Guillaume ; Greaves, Richard ; Tripier, Jeanne ; Klein, Yves ; Blank, Irma ; Mourand, Tania ; Hare, Chauncey ; Roussopoulos, Carole ; Arcier, Raymonde ; Isek Kingelez, Bodys ; Stojka, Ceija ; Cheval, Facteur ; Rama, Carol ; Vautier, Ben ; Broodthaers, Marcel ; Boltanski, Christian ; Bascoulard, Marcel ; Calle, Sophie ; Motti, Gianni ; Cattelan, Maurizio ; Vainity, Wendy ; Wölfli, Adolf ; Adéagbo, Georges ; Widener, George ; van Bender, Adelhyd ; Wang, Galaxia ; Emard, Justine
Often celebrated as a kind of genius trained in the “school of life” who managed to produce a singular body of work despite a lack of professional training, the autodidact questions and challenges our conceptions of art. Entitled The Self-taught Enigma, the new exhibition presented at the MAMC+ in Saint-Étienne aims to revisit this idealising vision of the figure of the self-taught artist in the history of contemporary art in an attempt to grasp what actually happens when artists learn by themselves. (provided by publisher)
boek